ChemInform Abstract: CuI‐Mediated α‐Ketoacylation of Sulfoximines under Solvent‐Free Conditions. Issue 47 (November 2015) - Zou, Ya; Peng, Zhihong; Dong, Wanrong; An, Delie
Abstract: A double catalytic cycle mechanism involving elemental iodine and copper is proposed.